Surface state on first-order ferroelectrics - Chew, Khian Hooi; Halif, M.N.A.; Osman, J.; Tilley, D.R.; Teh, R.; Ishibashi, Y. (2006)
In the presence of a surface the Landau-Devonshire equations of ferroelectricity must be extended to include a boundary condition. For a ferroelectric with a second-order transition in the case when the polarization p(z) increases at the surface, it is well known that a surface state occurs in a range of temperature above the bulk critical temperature t(CB) . Here we explore the corresponding effect for a first-order ferroelectric. We show that a surface state can occur, but only if the surface effect is sufficiently strong. Analytic expressions are derived and illustrated for p(z), the surface value p(S) =p(0) and the free energy. The transition from the paraelectric state (p=0) to the surface state is first order, and for completeness we establish the dependence of the three critical temperatures (supercooling, thermodynamic and superheating) on a boundary-condition parameter y. In a final section, we derive and illustrate expressions for p(z)in the temperature range t < t(CB) .